Long‐term follow‐up of lower dose dasatinib (50 mg daily) as frontline therapy in newly diagnosed chronic‐phase chronic myeloid leukemia. Issue 1 (25th September 2019) - Naqvi, Kiran; Jabbour, Elias; Skinner, Jeffrey; Anderson, Kristin; Dellasala, Sara; Yilmaz, Musa; Ferrajoli, Alessandra; Bose, Prithviraj; Thompson, Philip; Alvarado, Yesid; Jain, Nitin; Takahashi, Koichi; et al.
Abstract : Background: Dasatinib, a potent Bcr‐Abl tyrosine kinase inhibitor, is approved for the treatment of chronic‐phase chronic myeloid leukemia (CML‐CP) in the frontline and salvage settings. Notable side effects include pleural effusions and myelosuppression. Dasatinib at 50 mg daily has previously been reported to be active and better tolerated than the approved 100‐mg daily dose. The aim of this study was to update the long‐term follow‐up results of dasatinib at 50 mg daily as frontline therapy for CML‐CP. Methods: Eighty‐three patients with newly diagnosed CML‐CP received dasatinib at 50 mg daily. Eligibility and response criteria were standards used in previous protocols. Results: After a minimum follow‐up of 12 months, 81 patients were evaluable. Two patients came off the study in less than 3 months. The rates of BCR‐ABL1 transcript levels (International Standard) at ≤10% and ≤1% at 3 months were 96% and 77%, respectively. The cumulative rates for a complete cytogenetic response by 6 and 12 months were 77% and 95%, respectively. The cumulative rates for a major molecular response, a molecular response with a 4.0‐log reduction, and a molecular response with a 4.5‐log reduction by 12 months were 81%, 55%, and 49%, respectively. Twenty‐one patients (25%) had treatment interruptions for a median of 13 days (range, 4‐64 days). Five patients (6%) developed pleural effusions; 4 of these patients (80%) required a dose reduction. Two patients (2%) failed to achieve any cytogenetic or molecular response and were taken off the study. At a median follow‐up of 24 months, none of the patients had disease transformation to an accelerated or blastic phase. The 2‐year event‐free and overall survival rates were 100%. Conclusions: These updated results continue to support 50 mg of dasatinib daily as an effective and safe dose for early CML‐CP. Abstract : This study updates the long‐term follow‐up results for dasatinib at 50 mg daily as frontline therapy for chronic‐phase chronic myeloid leukemia. These updated results continue to support 50 mg of dasatinib daily as an effective and safe dose for early chronic‐phase chronic myeloid leukemia.